Novel Insights on Lipid Metabolism Alterations in Drug Resistance in Cancer - Yang, Ruixue; Yi, Mei; Xiang, Bo (Frontiers in Cell and Developmental Biology, 2022)
Chemotherapy is one of the primary treatments for most human cancers. Despite great progress in cancer therapeutics, chemotherapy continues to be important for improving the survival of cancer patients, especially for those who has unresectable metastatic tumors or fail to respond to immunotherapy. However, intrinsic or acquired chemoresistance results in tumor recurrence, which remains a major obstacle in anti-cancer treatment. The high prevalence of chemoresistant cancer makes it urgent to deepen our understanding on chemoresistance mechanisms and to develop novel therapeutic strategies. Multiple mechanisms, including drug efflux, enhanced DNA damage reparability, increased detoxifying enzymes levels, presence of cancer stem cells (CSCs), epithelial mesenchymal transition (EMT), autophagy, ferroptosis and resistance to apoptosis, underlie the development of chemoresistance. Recently, accumulating evidence suggests that lipid metabolism alteration is closely related to drug resistance in tumor. Targeting lipid metabolism in combination with traditional chemotherapeutic drugs is a promising strategy to overcome drug resistance. Therefore, this review compiles the current knowledge about aberrant lipid metabolism in chemoresistant cancer, mainly focusing on aberrant fatty acid metabolism, and presents novel therapeutic strategies targeting altered lipid metabolism to overcome chemoresistance in cancer.